Audience observations of art, identity and schizophrenia : possibilities for identity movement - Farquharson, Kirsten Leigh (Rhodes University, Faculty of Humanities, Department of Psychology, 2014)
This research situates itself in the study of stigma in mental illness. In particular, the aim is to explore the potential that art making and exhibiting has in reducing stigma for those with a diagnosis of schizophrenia. The research explores one aspect (the exhibition stage) of an "art as therapy" project. The exhibiting of one's artwork aims to counter limiting "patient" identities by allowing those labelled as psychiatric patients to extend their self-identity to an alternative identity of the "artist". However, this idea only stands strong if the artwork created is not discriminated against as "naïve art" and is accepted or at least considered for acceptance as legitimate nonprofessional artwork. This research explores the ways in which art created by inpatients with a diagnosis of schizophrenia is received by the general art-viewing public at the National Arts Festival in Grahamstown, South Africa. The study uses a discourse analytic framework to analyse the interviews of members of the public who attended the art exhibition of patient artwork. It will examine the ways in which the public construct the artworks and how they position the makers of this art across a continuum, from patient to artist. The results of this thesis have implications for rehabilitation practices for people with a diagnosis of schizophrenia particularly with regard to opportunities to "perform" alternative identities in public spaces.
Keywords: Mental illness -- Social aspects; Stigma (Social psychology); Identity (Psychology); Schizophrenia -- Treatment; Art therapy -- Research; Art, -- South African -- 21st century -- Exhibitions